Developing non-invasive molecular markers for early risk assessment of Alzheimer's disease - Tapas K. Sur; Tanmoy Mondal; Zarish Noreen; Jheannelle Johnson; Gail Nunlee-Bland; Christopher A. Loffredo; Brent E. Korba; Vijay Chandra; Siddhartha S. Jana; Bernard Kwabi-Addo; Sumit Sarkar; Somiranjan Ghosh (Biomarkers in Neuropsychiatry)
Alzheimer's disease (AD) is a heterogeneous neurodegenerative disease, with no standard biomarker(s) to detect or confirm its risk at an early stage. The prevalence of AD increases exponentially worldwide in people of ages over 65 and older. Current improvements have unveiled the disease's pathophysiology and clinical diagnostic tests, targeting the neurological changes (neurodegeneration, amyloid precursor protein metabolism and tangle pathology) with precise PET/MRI imaging and xMAP/SIMOA (Multiplex simultaneous detection/single molecule array) to identify and quantify β-amyloids (Aβ40, Aβ42), total tau (T-tau) and phosphorylated tau (P-tau) proteins in the brain and cerebrospinal fluid (CSF) of patients. However, their utility for diagnosis in routine clinical practice is still challenging because of cost, accessibility, standardization, procedural limitation, and regulatory approval. Further research is needed to establish affordable, patient-friendly, easy, quick, and robust biomarkers for early AD detection, progression, and therapeutic management. Research on blood-based preclinical diagnosis and clinical practice for AD has advanced significantly in the last decade. Emerging literature supports the importance of new molecular biomarkers and signature genes from blood to detect and predict AD in advance. This review examines the potential applications of these blood-based target biomarkers for early disease detection, co-morbid condition risk prediction, and treatment management of AD.